Effect of ethanol treatment on shrinkage of oil palm trunk for the drying process - Othman, Ahmad Fauzi; Arshad, Mohd Fadzil; Ahmad, Zakiah; Shafie, Amran; Ahmad Zaki, Junaiza; Abdul Latif, Nur Hannani; Mohamad, Mohd Azrul Naim (2022)
Oil palm trunk is one of the promising biomass materials due to the high volume of unused waste components and increasing worldwide demand to replace conventional wood. This study aimed to investigate the feasibility of using ethanol as a drying agent for oil palm trunks with different dimensional surfaces (radial, tangential and longitudinal sections). Radial shrinkage percentage for the outer layer is 1.50% (untreated) and 1.22 % (treated) respectively. In comparison, the inner layer of the untreated sample was recorded at 2.54 % shrinkage and the treated sample was at 2.29%. The tangential sample for the inner untreated sample shows 2.60% and the treated sample shows 2.40%. The same pattern of shrinkage was shown for the tangential section on the outer layer as 1.81% and 1.10% of the untreated and treated sample respectively. For the longitudinal surface, the inner layer section of the untreated sample was recorded at 0.39% compared to the treated sample at 0.25%. In comparison, a longitudinal surface section for the outer layer of the untreated sample was recorded at 0.38% while the treated sample was recorded at 0.33% shrinkage percentage. The effect of ethanol treatment on the shrinkage is significantly different between different sections (P-value: 0.01) and between the outer and inner layers (P-value: 0.02). The result suggested that ethanol treatment could be an option for the oil palm trunk drying process. Dried oil palm trunk can be utilized as a potential substitution of biomass and wood to produce various products.